2017
DOI: 10.1016/j.jtho.2017.09.1040
|View full text |Cite
|
Sign up to set email alerts
|

P1.15-004 An Open-Label, Multitumor Phase II Basket Study of Olaparib and Durvalumab (MEDIOLA): Results in Patients with Relapsed SCLC

Abstract: Background: Amrubicin is one of the most active chemotherapeutic agents for small-cell lung cancer (SCLC). Previous studies reported its effectiveness and severe hematological toxicity. However, the efficacy of amrubicin monotherapy in elderly patients with SCLC has not been described. The objective of this study was to investigate the feasibility of amrubicin monotherapy in elderly patients, and its efficacy for relapsed SCLC. Method: A retrospective cohort study design was used. We retrospectively evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
3
22
1
Order By: Relevance
“…However, these increases failed to correlate with T-cell infiltration. The disappointing response rates in this trial are similar to a previous phase II basket study including patients with relapsed SCLC that used the same doses of olaparib and durvalumab but with a 4-week olaparib run-in period [66]. These early results suggest that additional mechanisms suppress antitumor immunity in SCLC.…”
Section: Combining Parp and Immune Checkpoint Inhibitionsupporting
confidence: 70%
“…However, these increases failed to correlate with T-cell infiltration. The disappointing response rates in this trial are similar to a previous phase II basket study including patients with relapsed SCLC that used the same doses of olaparib and durvalumab but with a 4-week olaparib run-in period [66]. These early results suggest that additional mechanisms suppress antitumor immunity in SCLC.…”
Section: Combining Parp and Immune Checkpoint Inhibitionsupporting
confidence: 70%
“…Differences in the immune phenotype across the molecular aberrations, such as BRCA1, BRCA2, and mutations in the homologous recombination repair pathway, are known to infer response to PARPi. Such detailed understanding is required to predict to what extent PARP inhibitors may enhance response to immune checkpoint blockade, such as PD-L1 (50)(51)(52)(53), or other immunotherapy approaches.…”
Section: Adapting Clinical Trials Design For Immunotherapymentioning
confidence: 99%
“…A phase II trial of durvalumab in combination with olaparib for selected advanced solid cancers (MEDIOLA) showed that this combination is well tolerated with no significant overlapping toxicities (108)(109)(110)(111). Clinical response measured as disease control rate at 12 weeks was 29%, 80%, and 81% in patients with advanced SCLC, germline BRCA1/2-mutant HER2-normal breast cancer, and germline BRCA1/2-mutant platinum-sensitive ovarian cancer, respectively (109)(110)(111). This same combination was also assessed in patients with CRPC, and reported a 12-month PFS of 51% in a population unselected for DDR variants (112).…”
Section: Immune Checkpoint Inhibitor Combinationsmentioning
confidence: 99%